The embodiment of Dramatic Character dimensions in Faqi Tayran’s Epic "Shekhe San’an’s" - Hassan, Shivan Q.; Khalid (Agren), Abdullah A. (Humanities Journal of University of Zakho, 2018)
Faqi Tayran’s Epic “Shekhe San’an’s” is considered one of the well-known and great literary works in ancient Kurdish literature due to its dramatic structure and its possession of various practical artistic elements. These features could give a chance to present numerous studied to that elements. The character as an element can be regarded as an important one rather than the elements of text in dramatic text. Characters perform the process of dramatic acts and without characters there are no other elements in dramatic text such as dialogue, plot, event, conflict, tension …. etc. finally, without dramatic characters, the epic text is considered as a dead text that has no literary spirit and meaning. Generally, according to the importance of dramatic character is divided into main types; simple character complicated character. These two types, complicated character in particular, consisting of three main dimensions. These dimensions as Natural, Social, and Psychological ones, and among all these three dimensions, psychological one has a great importance to the dramatic characters. Due to the interests of dimensions that the mentioned epic has, we started to select a title to this study as entitled: The embodiment of Dramatic Character dimensions in Faqi Tayran’s Epic “Shekhe San’an’s”. The quantity of the embodiment of these three dramatic dimensions is stated throughout studying that epic as well as the clarification is presented so practically.